Folktales as a Medium for Group Guidance in Developing Empathy and Tolerance in Middle School Students: A Systematic Review - Novitasari, Yuni; Susanto, Eko (Sociometry Journal of Social Science, Art and Humanity, 2025)
This study aims to analyze the effectiveness of folklore as a medium for group guidance in developing empathy and tolerance in high school students through a PRISMA-based systematic literature review (SLR) approach. The search method was carried out using the Scopus database using keywords related to folklore, group guidance, empathy, and tolerance for the period 2010-2024 with a focus on post-2015 studies for quantitative and digital evidence. The selection results yielded 50 articles that met the inclusion criteria for further analysis. Thematic analysis revealed that the integration of folklore with pedagogical techniques such as values ​​clarification, sociodrama, and role-playing proved effective in developing empathy and tolerance in students. The psychosocial and neurocognitive mechanisms triggered by folklore support stereotype reduction, identity strengthening, and the development of social-emotional skills. The findings also indicate that digital storytelling is as effective as traditional methods, if not superior, in increasing student engagement and reflection. Key challenges include limited teacher training, limited cross-cultural research, and the lack of standardized measurement tools. Research recommendations lead to the development of an integrated curriculum, practice-based teacher training, the development of a digital platform, and the validation of a folklore-based empathy and tolerance measurement tool. These findings provide important implications for educational practitioners, school counselors, and policy makers in designing folklore-based interventions for character development and social-emotional competencies in secondary schools.